Improving patient-centered mental health promotion in primary care in vulnerable communities through mindfulness training in Rio de Janeiro, Brazil - Teixeira, Débora Silva; Fortes, Sandra; Kestenberg, Celia; Alves, Kali; Campos, Mônica Rodrigues; Neto, Alfredo Oliveira; Ortega, Francisco; García-Campayo, Javier; Demarzo, Marcelo (Frontiers in Medicine, 2024)
Introduction Brazilian Primary Health Care (PHC) is responsible for all-sanitary actions for a community-based population, including health promotion and mental health care. Mindfulness Based Health Promotion (MBHP) is an intervention that can promote self-care and psychosocial support in PHC. Objective To discuss the effects of mindfulness based psychosocial group interventions for health promotion in primary care units in Rio de Janeiro, Brazil. Methods The intervention was based on the MBHP model adapted for SUS. Nine groups were held in Rio de Janeiro. A quali-quanti research was held with two parts: (a) quantitative study, pre and after the 8 weeks intervention, evaluating the effect on mindfulness and self-compassion and their association with levels of anxiety, depression, and quality of life. (b) Qualitative research using Focus Groups with the participants to investigate their experience at the end of the mindfulness groups. Results and discussion Sixty-two participants finished the 9 groups where 86% were women, mostly between 30 and 59 years of age and low income, and around 80% under regular medical care in PHC in SUS. In the studied sample 80% had at least one chronic health condition under treatment, including 42% with anxiety and 35% with depression. The effects included significant improvement in Anxiety and Depression and in Quality of Life, mainly in the psychological but also in the physical and interrelation domains. The qualitative study showed that most patients joined the group on the recommendation of health professionals for managing physical and mental health symptoms. Patients reported being able to use the practices taught in the sessions to manage symptoms such as insomnia and emotionally distressing situations in their daily lives. Including family members in mindfulness practices was a strategy to negotiate not only a space at home to meditate, but also to obtain a different approach to health problems. Participants pointed to mindfulness as a complementary therapeutic option to medication and psychotherapy. Conclusion Mindfulness-Based Intervention have shown to be a feasible, well-accepted and efficacious method of offering psychosocial support and promoting well-being for low-income patients in primary care in LAMIC.